Risk-profile and outcome of small papillary and follicular thyroid carcinomas (≤1 cm) - Rahbar, K.; Hutzenlaub, V.; Fischer, R.-J.; Schober, O.; Riemann, B. (Nuklearmedizin - NuclearMedicine, 2008)
Aim: According to the procedure guidelines of the German Society of Nuclear Medicine no radioiodine ablation is necessary in patients with papillary microcarcinomas in case of limited surgical resection. Few data are available with respect to the optimal management of patients with small follicular thyroid carcinomas. It was the aim to compare risk-profile and outcome of patients with small papillary (PTC) and follicular thyroid carcinomas (FTC) ≤1 cm. Patients, methods: 1594 patients with thyroid cancer were attended at our department between 1995 and 2006. For the subgroup of 383 patients with small PTC and FTC ≤1 cm a comparative correlation of multifocality, extrathyroidal growth, lymph node spread, distant metastasis, local recurrence and survival was performed. Patients were monitored for a mean follow-up time of six years. Results: A total of 361 patients had PTC and 22 FTC ≤1 cm. At presentation the mean age of the 306 women and 77 men was 49 ± 13 years. An ablative radioiodine therapy was performed in 77% and 100% of patients with small PTC and FTC, respectively. Multifocality (14% vs. 9%), extrathyroidal growth (10% vs. 5%), lymph node spread (14% vs. 5%), local recurrence (0.5% vs. 0%) and progressive disease (1% vs. 0%) were more common in patients with small PTC than FTC, whereas the corresponding values for distant metastasis were 2% vs. 5%, respectively; however, these figures did not reach statistical significance. Eight patients with papillary microcarcinomas died because of nonthyroidal diseases. Conclusion: Our data show no statistically significant differences in the risk-profile and outcome of patients with small PTC and FTC ≤1 cm. Therefore, the decision for or against radioiodine ablation in patients with small differentiated thyroid carcinomas should be discussed individually.
Keywords: Radioiodine ablation; papillary and follicular thyroid carcinoma; tumour size; extrathyroidal growth; lymph node metastasis; distant metastasis; recurrence